A Kinetic Photometric Assay for the Quantification of the Open‐Chain Content of Aldoses. Issue 18 (8th April 2021) - Kalaus, Hubert; Reichetseder, Alexander; Scheibelreiter, Verena; Rudroff, Florian; Stanetty, Christian; Mihovilovic, Marko D.
Abstract: Aldoses exist predominantly in the cyclic hemiacetal form, which is in equilibrium with the open‐chain aldehyde form. The small aldehyde content hampers reactivity when chemistry addresses the carbonyl moiety. This low concentration of the available aldehyde is generally difficult to ascertain. Herein, we demonstrate a new kinetic determination of the (minute) open‐chain content (OCC) of aldoses. This kinetic approach exploits the aldehyde‐selectivity of 2‐aminobenzamidoxime (ABAO), which furnishes a strongly UV‐active adduct. Simple formation curves can be measured in a photometer or plate reader for high‐throughput screening. Under pseudo‐first order kinetics, these curves correlate with a prediction model yielding the relative OCC. The OCCs of all parent aldoses (pentoses and hexoses) were determined referencing against the two tetroses with exceptionally high OCCs and were in very good agreement with literature data. Additionally, the assay was extended towards higher‐carbon sugars with unknown OCC and also applied to rationalise a lack of reactivity observed in a recent synthetic investigation. Abstract : An operationally simple UV‐based kinetic assay allows the accurate determination of the minute proportions (<1 %) of the open‐chain forms (OCC) of aldoses in equilibrium with the dominant ring forms. The OCC‐data of all parent aldoses has been determined with this new ABAO‐assay and is fully consistent with the literature gold standard, allowing extension into first practical synthetic challenges.